Improving English Vocabulary of the Fifth Grade Students at Santa Monica Elementary School Through YouTube English Songs - Valentina Prawita Angkasa Pasaribu; Roihatul Millah; Widya Syafitri (Austronesian: Journal of Language Science & Literature, 2026)
This study examines the use of YouTube English Songs as a digital learning resource to enhance English vocabulary among fifth-grade students at Santa Monica Elementary School. Vocabulary mastery is a crucial component in English language learning, as it directly affects students’ ability to communicate and comprehend meaning. However, many students demonstrated limited vocabulary due to low engagement and passive participation during learning activities. This study aims to implement and evaluate YouTube English Songs as an instructional tool to improve students’ vocabulary. A Classroom Action Research (CAR) design with a qualitative approach was employed, involving 20 fifth-grade students across two cycles, each comprising the stages of planning, action, observation, and reflection. Data were collected through observation and pre-test and post-test instruments. The findings revealed that the use of YouTube English Songs significantly increased students’ engagement and motivation. Collaborative singing activities led to a substantial improvement in vocabulary knowledge, with average scores rising from 66.45 in the pre-test to 74.45 after Cycle 1, and further to 90.4 after Cycle 2. Challenges encountered included time management and the selection of songs aligned with learning themes. These findings indicate that learning vocabulary through English songs is an effective and enjoyable strategy that offers a dynamic alternative to conventional teaching methods. Educators are encouraged to integrate digital learning resources into their instructional practices, and further research is recommended to explore this approach across different educational contexts.